Analytical model for the Load-Slip behavior of headed stud shear connectors. (1st February 2022) - Meng, Hao; Wang, Wei; Xu, Rongqiao
Graphical abstract: Highlights: A new model is proposed for the load-slip behaviors of headed stud connectors. A model of beam rested on foundation is firstly developed for the shear connectors. More geometric and material parameters of connectors are considered in the model. The present model can be an alternative to the experimental and numerical methods. Abstract: Extensive push-out tests have been conducted to obtain the formulas for the strength, stiffness, and load-slip curve of headed stud shear connectors through curve regression for parameters including concrete strength, stud strength, and stud diameter. However, due to the limitation of conditions in tests, the application range of these formulas is limited and there is a lot of discrepancies among them. This work proposes an analytical model to describe the shear behaviors of headed stud shear connectors by analyzing the load-slip curves and failure modes in the literature. The stud and surrounding concrete are idealized as a model of beam rested on foundation, whose equivalent stiffness is analytically determined by a function of the stud diameter, stud length, and parameters reflecting material properties of the stud and concrete. Therefore, the whole load-slip curve is directly obtained according to the material and geometric parameters of the headed stud shear connector. Numerical examples show that the present model can predict the load-slip curve in good agreement with the existing experimental data. Finally, the effects of material and geometry of shear connectors on their shear behaviors are discussed parametrically.